The Status of Serum Zinc, Magnesium and Calcium in Type 2 Diabetic Patients and Their Correlation with Renal Function. - Hami, Mohammed A.; Ibrahim, Aveen A.; Ahmed, Maysoon S. (Science Journal of University of Zakho, 2016)
Trace elements play significant roles in the metabolism of insulin. The aim of this study is to investigate the level of serum zinc, magnesium and calcium in type 2 diabetes mellitus and relate them with the functionality of kidneys. 200 diabetic individuals and 50 healthy controls were enrolled. For each individual, blood sugar, serum urea and serum creatinine were determined. In addition, serum zinc, magnesium and calcium were determined for each individual via flame atomic absorption spectrometry. Significant differences were found in the level of serum zinc and magnesium between diabetic and healthy control groups. However, there was not any difference in the level of serum calcium between the two groups. It is not certain whether the low level of serum zinc and magnesium cause diabetes or they are the consequence of development of diabetes. The level of serum trace elements did not correlate with the functions of kidneys.